Enrique Desmond Arias, Criminal Enterprises and Governance in Latin America and the Caribbean, Cambridge, Cambridge University Press, 2017, 302 pp. - Bonilla Alguera, Gerardo (Gestión y Política Pública, 2020)
Reseña del libro Criminal Enterprises and Governance in Latin America and the Caribbean de Enrique Desmond Arias.